“When the Government Changes, the Card Will Also Change”: Questioning Identity in Biometric Smartcards for National Health Insurance (RSBY) in India - Ecks, Stefan (Anthropologica, 2018)
Since the mid-2000s, government initiatives in India have been gripped by the idea that biometric identification is more efficient than any form of paper-based documentation. In this article, I explore how new health care schemes in India have adopted this technocratic promise. On the basis of ethnographic research in Karnataka, I describe how enrolments for biometric smartcards for RSBY insurance proceeds. These enrolments are meant to turn the rural poor into consumer citizens, yet the RSBY cards elicit unexpected responses from the beneficiaries. Instead of reproducing state authority, the new ID cards become a fulcrum for questioning the stability of government.